Theoretical Aspects of the Legislation Dealing with Proceedings Regarding Criminal Property - Kaija, Sandra; Kudeikina, Inga (European Journal of Sustainable Development, 2021)
The research deals with problems relating to proceedings regarding criminal property, as a result of which property may be recognised as criminally derived and be forfeited. It should be noted that matters at hand are interdisciplinary and require a systemic approach. The research focuses on procedural aspects of criminal property forfeiture in the context of an individual’s right to property. The forfeiture of criminal property by way of special proceedings before a court judgement resulting in criminal conviction becomes final is an adequate means of criminal proceedings, whose main goal is to restore justice between parties to criminal proceedings by returning criminal property to the lawful owner as soon as possible. However, it should be considered that this type of property forfeiture has a dual nature, namely: the legislation should also secure the rights of persons having opposite interests, such as the alleged offender, the property owner affected by criminal proceedings and the victim.